Chaotic Dynamics on Air Quality and Human Health: Evidence from China, India, and Turkey - Bildirici, Melike E. (SOC CHAOS THEORY PSYCHOLOGY & LIFE SCIENCES, 2021)
The chaotic structure of air pollution, human health, the evidence of cointegration and causality between the air pollution, transportation, tourism, construction, and manufacturing industries and the evidence of cointegration and causality between the air pollution, transportation, tourism, construction, and manufacturing industries and mortality rate were explored for China, India, and Turkey in the period of 1975-2018 by using four different methods. Firstly, Lyapunov and Shannon tests were applied to determine chaotic dynamics. The maximum Lyapunov test, for the selected variables, found the evidence of chaotic dynamics. Secondly, Fourier ADF and NL tests were applied. Fourier unit root test determined stationary of the variables. Thirdly, bootstrapping autoregressive distributed lag with Fourier transformation (FBARDL) was used to determine the evidence of cointegration between the variables with two different models. FBARDL test determined that the manufacturing, tourism, transport, and construction industries, air pollution, and mortality rate have evidence of cointegration in different two models. Lastly, the causality test with Fourier transformation was used to determine the direction of causality between the variables. Granger causality test determined that there is evidence of one-way causality running from transportation, tourism, construction, and manufacturing industries to air pollution and mortality rates. Accordingly, the results of this paper suggest air pollution and human health have chaotic behaviors. Air pollution has a complex, multi-variable, and multi-coupling system. Air pollutants influencing factors and air pollution itself have adverse effects on human health.
Keywords: Key Words; chaotic behavior; Fourier Bootstrapping Auto Regressive Distributed Lag (FBARDL); human health; air pollution; GLOBAL CO2 EMISSIONS; LOW-BIRTH-WEIGHT; CEMENT PRODUCTION; PRETERM BIRTH; PARTICULATE MATTER; ENERGY-CONSUMPTION; POLLUTION; ASSOCIATION; POLLUTANTS; MORTALITY; Mathematical Methods In Social Sciences; Psychology